Lan truyền thông tin trong khủng hoảng thực phẩm: Phân tích nội dung về thịt heo dịch bệnh trên nền tảng TikTok và YouTube tại Việt Nam - Hoàng, Anh; Trịnh Nữ , Nhi; Vũ Thị Thanh, Tú; Phạm Việt, Hải (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
The development of social media has fundamentally changed the way crisis information is generated, disseminated, and received. This study analyzes the roles of TikTok and YouTube in disseminating information about Group X’s "sick pork" crisis in Vietnam using network analysis. Data were collected from May 30 to June 15, 2025, including user–hashtag networks on TikTok (584 nodes, 726 edges) and video-level data on YouTube (60 videos). The study uses graph theory metrics such as centrality, betweenness, closeness, and PageRank, community detection using the Louvain algorithm, and force-directed layout visualization. For YouTube, the study adds temporal analysis, keyword extraction, and comment sentiment analysis. The results show that TikTok spreads information quickly due to its recommendation and hashtag mechanisms, while YouTube promotes in-depth discussions and clearly reflects community sentiment. Both platforms complement each other in shaping and amplifying crisis messages. The study recommends that businesses and regulators monitor multiple platforms, tailor responses to channel characteristics, and apply network analytics to identify key actors, mitigate negative impacts, and support crisis communications.